Empowerment and Social Skill Development of People with Disabilities in the Sahabat Difabel Community - Sahana Nadila Syafa Kamila; Harto Wicaksono (Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Persons with disabilities often face negative stigma and challenges in developing their potential due to limited access to appropriate education and training. Despite the growing body of literature on disability empowerment, existing studies have predominantly focused on hard skill development and economic outcomes, while the role of social skills programs in facilitating broader social integration remains underexplored. This study aims to analyze the empowerment and social skill development of persons with disabilities through programs implemented by the Sahabat Difabel Community, employing the theory of secondary socialization proposed by Berger and Luckmann (1966) and the critical pedagogy framework of McLaren (2010). Using a descriptive qualitative method, data were collected through interviews, observations, and documentation from November 2024 to June 2025 in Semarang. The findings indicate that the community provides both hard skill and soft skill training to support the independence and social skills of persons with disabilities. This potential-based empowerment model emphasizes social inclusion and work readiness while complementing the role of families in fostering independence. The study recommends further collaboration among communities, families, private institutions, and the government to create an inclusive environment that supports the development of persons with disabilities.